(untitled) (Global Journal of Management and Business Research, 2022)
This study compares the performance of stateowned firms local government SOEs and privately-owned firms in China Using panel data comprising 13 273 firm-year observations for the period 2005-2012 and OLS 2SLS and difference-in-difference regression we report that the identity of the largest shareholder does matter Our results show that the listed central government-owned SOEs operating costs are similar to those of local government owned SOEs and privately-owned firms Our results suggest that ownership concentration matters in China that is central government shareholding is an important determinant of state owned firms performance The policy implication of this study is that helping-hand and protectionist policies have helped stateowned firms to prosper in by creating an uncompetitive market and ineffective legal infrastructure